Culturing Bioscience : A Case Study in the Anthropology of Science - Krautwurst, Udo R. (Udo Rainer), 1959- (Book collections on Project MUSE., 2014)
"Charting the rise and fall of an experimental biomedical facility at a North American university, Culturing Bioscience offers a fascinating glimpse into scientific culture and the social and political context in which that culture operates. Krautwurst nests the discussion of scientific culture within a series of levels from the lab to the global political economy. In the process he explores a number of topics, including: the social impact of technology; researchers' relationships with sophisticated equipment; what scientists actually do in a laboratory; what role science plays in the contemporary university; and the way bioscience interacts with local, regional, and global governments. The result is a rich case study that illustrates a host of contemporary issues in the social study of science."--Publisher's description